2021
DOI: 10.1101/2021.11.23.21266785
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Randomized Clinical Trial of 2-Week Methotrexate Discontinuation in Rheumatoid Arthritis Patients Vaccinated With Inactivated Sars-Cov-2 Vaccine

Abstract: ObjectivesTo evaluate the effect on immunogenicity and safety of 2-week methotrexate(MTX) discontinuation after each dose of the Sinovac-CoronaVac vaccine versus MTX maintenance in rheumatoid arthritis(RA) patients.MethodsThis was a single-center, prospective, randomized, investigator-blinded, intervention study (#NCT04754698, CoronavRheum), including adult RA patients(stable CDAI<10, prednisone<7.5mg/day), randomized(1:1) to withdraw MTX(MTX-hold) for 2 weeks after each vaccine dose or maintain MTX(MTX-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…This finding is superior to the 47%–68% rate of positive antibodies reported for transplant recipients after mRNA additional dose25 28 29 45 and may be explained in part by the distinct intensity of immunosuppression, with a high frequency of multiple drug therapy in transplanted population. In addition, the temporary discontinuation of MTX and MMF in more than half of patients under these therapies might also have contributed to improved immune response, as reported recently by our group in rheumatoid arthritis population 46. The higher rates of anti-SARS-CoV-2 seropositivity in patients who withheld MMF herein were statistically not significant, probably due to a limited power for this analysis.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…This finding is superior to the 47%–68% rate of positive antibodies reported for transplant recipients after mRNA additional dose25 28 29 45 and may be explained in part by the distinct intensity of immunosuppression, with a high frequency of multiple drug therapy in transplanted population. In addition, the temporary discontinuation of MTX and MMF in more than half of patients under these therapies might also have contributed to improved immune response, as reported recently by our group in rheumatoid arthritis population 46. The higher rates of anti-SARS-CoV-2 seropositivity in patients who withheld MMF herein were statistically not significant, probably due to a limited power for this analysis.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, the temporary discontinuation of MTX and MMF in more than half of patients under these therapies might also have contributed to improved immune response, as reported recently by our group in rheumatoid arthritis population. 46 The higher rates of anti-SARS-CoV-2 seropositivity in patients who withheld MMF herein were statistically not significant, probably due to a limited power for this analysis.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Aroujo et al. reported that stopping MTX for 2 weeks after COVID-19 inactivated vaccination increased antibody titres, seroconversion rates, and RA flares [ 20 ]. It is theoretically uncontroversial that the temporary cessation of drugs that reduce antibody titres can improve antibody titres to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…A study performed in Hong Kong using administrative data among 5493 RA patients showed no association between vaccine receipt and RA flare as well as no difference in RA drug prescriptions after vaccination 44 . However, a randomized trial of holding vs. continuing methotrexate in RA patients after COVID-19 vaccine did show higher disease activity in those who held methotrexate 45 . This suggests that immunosuppressive medication changes around vaccination, rather than vaccine-specific effects, could explain at least some RMD flares after vaccination.…”
Section: Disease Flares After Sars-cov-2 Vaccine Seriesmentioning
confidence: 93%